Relationship Between Pregnant Mothers' Nutritional Status and the Event of Malnutrition in Babys - Indriani Hippy; Tut Rayani Aksohini Wijayanti; Sulistiyah Sulistiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
The nutritional status of pregnant women, assessed using the Upper Arm Circumference (LILA), plays a crucial role in fetal growth and birth outcomes. Inadequate maternal nutrition can lead to low birth weight, which increases the risk of stunting a condition characterized by a height-for-age (TB/U) less than -2 SD. Stunting is associated with a fourfold increase in child mortality under five years old, highlighting its significant impact on public health. This quantitative case-control study aimed to examine the relationship between maternal nutritional status during pregnancy and the incidence of stunting in toddlers. The study was conducted from August 25, 2024, to January 24, 2025, at Gogagoman Health Center in Kotamobagu City. A total of 60 toddlers participated, with 30 stunted toddlers (case group) and 30 non-stunted toddlers (control group). Data were collected through self-administered questionnaires, medical records, and microtoise measurements. The study employed univariate and bivariate data analysis, using a chi-square test to explore the association between maternal nutritional status and stunting incidence. The results indicated that the majority of respondents had adequate (non-KEK) maternal nutritional status. Specifically, 40% of mothers in the stunted group were classified as non-KEK, while 83.3% of mothers in the non-stunted group were in the same category. A statistically significant association was found between maternal nutritional status and the incidence of stunting, with a p-value of 0.010. These findings underscore the importance of improving maternal nutrition to prevent stunting and its associated risks. The study recommends collaborative efforts between health centers and local governments to provide targeted nutrition education and support for pregnant women and women of reproductive age, aiming to reduce stunting incidence and improve child health outcomes.